Constraint Annealing of HfO2 Films on Silicon Substrate: Suppression of Si Outward Emission. Issue 2 (10th January 2013) - Shih, Chuan‐Feng; Hsiao, Chu‐Yun; Chen, Bo‐Cun; Hsiao, Yu‐Chih; Leu, Ching‐Chich; Paranthaman, P.
<x xml:space="preserve">Abstract</x> Flexural tensile and compressive constraints were applied mechanically to the 7.5 nm thick HfO2 films on Si substrates to investigate the influences of stress on the Si outward emission behavior in Si/HfO2 during annealing. The constraint stress inhibited further growth of the interfacial layer (IL) between HfO2 and Si, suppressing the IL‐growth‐induced Si outward emission. This fact was associated with atomic rearrangement that was induced during constrained annealing, resulting in the formation of a robust HfO2 layer with low oxygen vacancy. Such an HfO2 layer effectively suppressed the inward diffusion of oxygen, the IL growth and the Si out‐diffusion.